OP0017 THERAPEUTIC DRUG MONITORING COMPARED TO STANDARD TREATMENT OF PATIENTS STARTING INFLIXIMAB THERAPY: RESULTS FROM A MULTICENTRE RANDOMISED TRIAL OF 400 PATIENTS. (2nd June 2020) - Syversen, S. W.; Goll, G. L.; Jørgensen, K. K.; Sandanger, Ø.; Sexton, J.; Olsen, I.; Gehin, J.; Brun, M. K.; Warren, D.; Mørk, C.; Kvien, T. K.; Jahnsen, J.; et al.
Abstract : Background: A lack or loss of response to TNFα inhibitors (TNFi) has been associated with low serum drug levels and formation of anti-drug antibodies (ADAb). Therapeutic drug monitoring (TDM), an individualised treatment strategy based on regular assessments of serum drug levels, has been suggested to optimise efficacy of TNFi. It is still unclear if TDM improves clinical outcomes, and the value of TDM has recently been included in the research agenda across different specialities. This first randomised controlled trial on the effectiveness of TDM in a range of immune mediated inflammatory diseases including rheumatic diseases, the NORwegian DRUg Monitoring trial part A (NOR-DRUM (A)) focus on the induction period of infliximab (INX) treatment. Objectives: To assess if TDM is superior to standard treatment in order to achieve remission in patients starting INX. Methods: In the investigator-initiated, randomised, open-label, multicentre NOR-DRUM (A) study, adult patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), spondyloarthritis (SpA), ulcerative colitis (UC), Crohn's disease (CD) and psoriasis (Ps) starting INX therapy were randomly assigned to administration of INX according to a treatment strategy based on TDM (TDM arm) or to standard administration of INX without TDM (control arm). Study visits were conducted at each infusion. The primary endpoint was remission at week 30. In the TDM arm, the dose and interval were adjusted according to INX trough levels to reach the therapeutic range (Figure 1 ). If the patient developed significant levels of ADAb, INX was terminated. To guide the investigators, the TDM strategy was integrated in an interactive eCRF. The primary endpoint was analysed by mixed effect logistic regression in the full analyses set (FAS), adjusting for diagnoses. Infections and infusion reactions were specified as adverse events (AEs) of special interest. Clinical trial.gov: NCT03074656 Results: We enrolled 411 patients at 21 study centres between January 2017 and December 2018. 398 patients (RA 80, PsA 42, SpA 117, UC 80, CD 57, Ps 22) received the allocated strategy and were included in the FAS population. Demographic and baseline characteristics were comparable in both arms. TDM was not found to be superior to standard treatment with regard to the primary outcome. Remission at week 30 was reached in 100 (53%) and 106 (54%) of the patients in the TDM and control arm, respectively (adjusted difference, 1.5%; 95% confidence interval (CI), -8.2 to 11.1, p=0.78) (Figure 2 ). Consistent results were shown for all the secondary endpoints (Figure 3 ) and in the sensitivity analyses. Twenty patients (10%) in the TDM arm and 30 patients (15%) in the control arm developed significant levels of ADAb. The number of adverse events (AE) was similar in both groups, however infusion reactions were less frequent (5 patients (2.5%) vs 16 patients (8.0%)) in the TDM arm (difference 5.5% (95% CI 1.1, 9.8%)) Conclusion: NOR-DRUM (A) is the first randomised trial to address effectiveness of TDM in the induction period of TNFi treatment, and the first trial to address TDM in rheumatic diseases. In this study, TDM was not superior to standard treatment in order to achieve remission. Although improved safety is indicated by a reduction in infusion reactions, implementation of TDM as a general strategy in the induction period of INX is not supported by the NOR-DRUM (A) study. Disclosure of Interests: Silje Watterdal Syversen Speakers bureau: Roche, Thermo Fisher, Guro Løvik Goll Consultant of: Novartis, Pfizer, Speakers bureau: Abbvie, Biogen, Boehringer Ingelheim, Orion Pharma, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, Kristin Kaasen Jørgensen Consultant of: AOP Orphan, Celltrion, Sandoz, Speakers bureau: Norgine, Tillots, Øystein Sandanger: None declared, Joe Sexton: None declared, Inge Olsen: None declared, Johanna Gehin Speakers bureau: Roche, Marthe Kirksæther Brun: None declared, David Warren: None declared, Cato Mørk Consultant of: Abbot, Novartis, Celagene, Almiral, Galderma, ACO, Almiral, ACO, Speakers bureau: Novartis, Abbott, Abbvie, Celegene, LEO, Almiral, Galderma, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Jørgen Jahnsen Consultant of: AbbVie, Boerhinger Ingelheim, Celltrion, Ferring, Janssen, Meda, MSD, Norgine, Novartis, Orion Pharma, Pfizer, Pharmacosmos, Takeda, and Sandoz., Speakers bureau: AbbVie, Astro Pharma, Boerhinger Ingelheim, BMS, Celltrion, Ferring, Hikma, Janssen, Meda, MSD, Napp Pharma, Orion Pharma, Pfizer, Pharmacosmos, Roche, Takeda, Tillotts and Sandoz, Nils Bolstad Consultant of: Pfizer, Janssen, Speakers bureau: Orion Pharma, Napp Pharmaceuticals, Takeda, Roche, Novartis, Espen A Haavardsholm Grant/research support from: AbbVie, UCB Pharma, Pfizer Inc, MSD Norway, Roche Norway, Consultant of: Pfizer, AbbVie, Janssen-Cilag, Gilead, UCB Pharma, Celgene, Lilly, Paid instructor for: UCB Pharma, Speakers bureau: Pfizer, AbbVie, UCB Pharma, Celgene, Lilly, Roche, MSD